Phonologie et morphosyntaxe de l'anglais dans un produit SIC : le premier module de MACAO - Cécile Poussard; Laurence Vincent-Durroux (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
French students who have English as part of their curriculum often express the wish to improve their comprehension of oral English. This led us to envisage the creation of a CALL product: MACAO (Modules to help in the comprehension of oral English). The first module has been created: "Training oneself for recognition". The computer was particularly adequate in this prospect. In this paper we present the most frequent difficulties in the comprehension of oral English: they can be related either to erroneous expectations based on the dissymmetry between the written form and the oral form of the language, or to the existence of context-based phonological variants as well as phonological resemblance of certain morphemes, which makes them difficult to identify. We also present how the content of the first module is an attempt to bring about solutions to these difficulties, by getting learners to have a better awareness of the existence of weak forms and unstressed syllables, be it in words or in monosyllabic words inserted in a sentence, and by offering the possibility to train themselves for the recognition of such elements. The module is presently being validated with a phase of evaluation.